Factors affecting biochemical recurrence time in prostate cancer patients: A single center analysis (Annals of Medical Research, 2022)
Aim: In this study, patients who underwent salvage Radiotherapy (RT) after biochemical recurrence (BCR) were evaluated retrospectively. The aim of this study was to evaluate the factors affecting the time to biochemical recurrence and salvage RT after radical prostatectomy.Materials and Methods: In Ankara Atatürk Education Hospital, patients with prostate cancer who received salvage RT between 01.01.2011 and 01.01.2018 were analyzed retrospectively. Patients who had undergone radical prostatectomy for prostate adenocarcinoma, and received salvage RT for PSA (Prostate-specific antigen) recurrence, were included. Patients who received post-surgery hormone therapy, and received definitive or palliative RT, were excluded. SPSS Ver. 22 software package was used for statistical analysis and the statistical significance limit was accepted as p≤0.05.Results: Results of 84 patients who met the criteria of the study were analyzed. The median follow-up was 78.5 (range 28-172) months and the median time between surgery and RT was 23.7 (range 5.1-136.9) months. The relationship between the time from surgery to BCR and the Gleason Score (GS) was statistically significant; the median time was 16.3 (2.17-125.9) months in the group with GS ≤8, and 8.9 (2.8-20.3) months in the group with GS 9-10 (p=0.05). The relationship between the time from surgery to BCR and T stage was statistically significant. In subgroup analysis, this difference was seen between T3A and T3B stages. That time was 17.8 (range 2.17-73.77) months in T3A and 8.7 (range 2.8-29.6) months in T3B stages (p=0.02). The relationship between the level of nadir PSA and the median time between surgery and BCR was significant. It was median 20.6 (range 5.4-65.2) months in patients with PSA< 0.03 and 8.8 (range 2.2-125.9) months in patients with PSA ≥0.03 (p
Keywords: Prostate Cancer; Salvage Radiotherapy; Biochemical Recurrence